Sugar Hacienda of the Marqueses Del Valle. - Barrett, Ward J. (University of Minnesota Press, 1970)
This is a detailed history of a Mexican sugar plantation, the first such account to be published in English. The subject of the study is the Cortes plantation, which was established on the outskirts of Cuernavaca in about 1535 by Hernan Cortes, the conque.